Ko te amorangi ki mua, ko te hāpai ō ki muri: The Role of Mātauranga Raranga in the Dissemination of Mātauranga Māori - Lentfer, Ngarongoa Isabella (Auckland University of Technology, 2015)
Indigenous knowledge comes not from one individual, but from a collective (Lentfer, 2012). Creation stories, cryptic proverbs or whakataukī, songs filled with imagery, symbolism and social value; tribal histories and ceremony were all integrated into everyday activities to inform kaupapa Māori or Māori philosophy and ideology. These can be seen as exemplars that informed cultural values, social interaction and protocols. In addition, analogy and personification of the natural world feature strongly in those expressions and all help to shape individual attitudes towards the care and preservation of the collective group. Māori art forms such as Raranga (to weave; traditional Māori art forms of weaving) are a visual means of communicating this Māori world view. Hence it is important to keep these traditional art forms alive and relevant to today?s constantly evolving Māori society. This research will critically examine the interconnectivity and relationships between Raranga and m?tauranga Māori (Māori knowledge) as a valid methodology and pedagogy for the transmission and dissemination of mātauranga Māori. Accompanied with the written work will be an art piece incorporating traditional raranga and tukutuku (lattice work) practices. The artefact itself represents a three dimensional view of Te kawau mārō, a model adapted by the researcher to illustrate the multiple layers of the methodology and pedagogy.
Keywords: Raranga; Pedagogy; Māori development; Mātauranga Raranga